Proposed Security Model and Threat Taxonomy for the Internet of Things (IoT) - Babar, Sachin; Mahalle, Parikshit; Stango, Antonietta; Prasad, Neeli; Prasad, Ramjee (Recent Trends in Network Security and Applications, 2010)
IoT is an intelligent collaboration of tiny sensors and devices giving new challenges to security and privacy in end to end communication of things. Protection of data and privacy of things is one of the key challenges in the IoT. Lack of security measures will result in decreased adoption among users and therefore is one of the driving factors in the success of the IoT. This paper gives an overview, analysis and taxonomy of security and privacy challenges in IoT. Finally, Security Model for IoT has been proposed.